2016
DOI: 10.1038/srep33216
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain ion gradients following compensation for elevated CO2 are linked to behavioural alterations in a coral reef fish

Abstract: Neurosensory and behavioural disruptions are some of the most consistently reported responses upon exposure to ocean acidification-relevant CO2 levels, especially in coral reef fishes. The underlying cause of these disruptions is thought to be altered current across the GABAA receptor in neuronal cells due to changes in ion gradients (HCO3− and/or Cl−) that occur in the body following compensation for elevated ambient CO2. Despite these widely-documented behavioural disruptions, the present study is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 67 publications
(127 reference statements)
1
59
0
Order By: Relevance
“…Exposure to high CO 2 levels triggers acid–base adjustments in fish involving altered levels of Cl − and HCO 3 − (Brauner and Baker, 2009), which have been suggested to change neuronal membrane gradients of these ions, switching some GABA A receptors from being inhibitory to excitatory (Nilsson et al ., 2012). Based on the scarce data available, calculations of GABA A equilibrium potentials of neurons in fish exposed to near-future pCO 2 are consistent in showing a possibility for a shift in the GABA A receptor equilibrium potential from causing hyperpolarization to depolarization (Heuer and Grosell, 2014; Nilsson and Lefevre, 2016; Heuer et al ., 2016; Regan et al ., 2016). Here, we hypothesized that an increase in CO 2 levels in the marine environment, triggering acid–base regulatory mechanisms in fish, could lead to changes in the expression of genes involved in regulating GABA A receptor function and neuronal ion distribution.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Exposure to high CO 2 levels triggers acid–base adjustments in fish involving altered levels of Cl − and HCO 3 − (Brauner and Baker, 2009), which have been suggested to change neuronal membrane gradients of these ions, switching some GABA A receptors from being inhibitory to excitatory (Nilsson et al ., 2012). Based on the scarce data available, calculations of GABA A equilibrium potentials of neurons in fish exposed to near-future pCO 2 are consistent in showing a possibility for a shift in the GABA A receptor equilibrium potential from causing hyperpolarization to depolarization (Heuer and Grosell, 2014; Nilsson and Lefevre, 2016; Heuer et al ., 2016; Regan et al ., 2016). Here, we hypothesized that an increase in CO 2 levels in the marine environment, triggering acid–base regulatory mechanisms in fish, could lead to changes in the expression of genes involved in regulating GABA A receptor function and neuronal ion distribution.…”
Section: Discussionmentioning
confidence: 91%
“…Heuer et al . (2016) showed that the increase in plasma partial pressure of CO 2 (in millimetres of mercury) in spiny damselfish ( Acanthochormis polyacanthus ) kept in high-CO 2 conditions was accompanied by increases in intracellular and extracellular HCO 3 − concentrations, with an assumed decrease in intracellular Cl − (Heuer et al ., 2016). Based on their measurements, they calculated a positive deviation in the E GABAA resting potential in fish exposed to 1900 µatm CO 2 , consistent with a shift in the GABA action towards depolarization (excitation) rather than hyperpolarization (inhibition).…”
Section: Discussionmentioning
confidence: 99%
“…This complex network of millions of neurons responsible for altering body patterns in cephalopods contain “all of the ‘classic’ neurotransmitters”, including γ‐aminobutyric acid (GABA) which are distributed throughout all neural lobes controlling chromatophore function (Messenger, ). GABA‐A receptors are important in this context as they appear to be responsible for the behavioural changes in other molluscs (Watson et al., ) and fishes (Hamilton, Holcombe, & Tresguerres, ; Heuer, Welch, Rummer, Munday, & Grosell, ; Lai, Jutfelt, & Nilsson, ; Nilsson et al., ) resulting from elevated CO 2 . Recent molecular analyses also demonstrate that substantial changes to GABA pathways are a feature of high CO 2 exposure in other invertebrates (Moya et al., ) and fish (Schunter et al., ), further supporting a role in behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
“…P CO2 between 600 and 2000 µatm). The pattern that emerged was complete regulation of blood plasma pH and a 2-5 mmol l −1 increase in blood plasma [HCO 3 − ] Esbaugh et al, 2016Esbaugh et al, , 2012Green and Jutfelt, 2014;Heinrich et al, 2014;Heuer et al, 2016;Strobel et al, 2012) (Table 1). Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…To our knowledge, only Heuer et al (2016) have estimated A-B parameters in the brains of fish exposed to OA-relevant P CO2 levels. and theoretical GABA A R Cl − and HCO 3 − permeability ratios, the results generally supported the GABA A R model.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%